Beer-Sheba III : The Early Iron IIA Enclosed Settlement and the Late Iron IIA-Iron IIB Cities - Hertsog, Zeʾev (Tel Aviv University Monograph Series, 2016)
Intro -- CONTENTS -- PREFACE -- CHAPTER 1: GENERAL INTRODUCTION -- CHAPTER 2: TOPOGRAPHY AND STRATIGRAPHY -- APPENDIX 2.1: CHALCOLITHIC OBJECTS IN THE IRON AGE STRATA -- CHAPTER 3: THE NORTHERN QUARTER -- CHAPTER 4: THE EASTERN QUARTER -- CHAPTER 5: THE SOUTHERN QUARTER -- CHAPTER 6: THE BASEMENT BUILDING AREA -- CHAPTER 7: THE CENTRAL QUARTER -- CHAPTER 8: THE WESTERN QUARTER -- CHAPTER 9: THE WATER SUPPLY -- REFERENCES -- CONTENTS -- CHAPTER 10: THE IRON IIA AND IIB POTTERY: AN INTRODUCTION -- CHAPTER 11: POTTERY FROM STRATA VII-IV: THE IRON IIA PERIOD -- CHAPTER 12: POTTERY FROM STRATA III-I: THE IRON IIB PERIOD -- CHAPTER 13: POTMARKS -- CHAPTER 14: STANDARDIZATION AND MASS PRODUCTION -- CHAPTER 15: VOLUME MEASUREMENTS -- CHAPTER 16: PETROGRAPHIC ANALYSES -- CONTENTS -- CHAPTER 17: CUNEIFORM INSCRIPTION -- CHAPTER 18: A SOUTH ARABIAN INSCRIPTION -- CHAPTER 19: THE GLYPTIC MATERIAL -- CHAPTER 20: EGYPTIAN OBJECTS -- CHAPTER 21: CLAY FIGURINES -- CHAPTER 22: SCALE WEIGHTS -- CHAPTER 23: METAL OBJECTS -- APPENDIX 23.1: CHEMICAL COMPOSITION OF COPPER-BASED OBJECTS -- CHAPTER 24: BEER-SHEBA UNDER ATTACK: A STUDY OF ARROWHEADS AND THE STORY OF THE DESTRUCTION OF THE IRON AGE SETTLEMENT -- CHAPTER 25: ALTARS AND ART OBJECTS -- CHAPTER 26: STONE TOOLS -- CHAPTER 27: WORKED BONE AND IVORY OBJECTS -- CHAPTER 28: TEXTILE-RELATED OBJECTS -- CHAPTER 29: TEXTILE REMAINS AND TEXTILE IMPRESSIONS -- CHAPTER 30: JEWELRY -- CHAPTER 31: ARCHAEOZOOLOGICAL FINDS FROM STRATA IX-III AND I -- CHAPTER 32: THE FAUNAL REMAINS FROM STRATUM II -- CHAPTER 33: ARCHAEOBOTANICAL REMAINS -- CHAPTER 34: EVIDENCE FOR IRON WORKING -- CHAPTER 35: HOUSEHOLD ACTIVITIES -- CHAPTER 36: SOCIAL, HISTORICAL AND CULTURAL RAMIFICATIONS -- CHAPTER 37: RECONSTRUCTING TEL BEER-SHEBA: CONCEPTUAL AND TECHNOLOGICAL ISSUES IN SITE PRESERVATION -- LIST OF LOCI -- Blank Page -- Blank Page.